2022
DOI: 10.21273/horttech04924-21
|View full text |Cite
|
Sign up to set email alerts
|

An Apple Tree Branch Pruning Analysis

Abstract: ADDITIONAL INDEX WORDS. automated pruning, branch cutting, branch diameter, cutting angle, Malus ×domestica, pruning end-effector, pruning force, pruning torque, robotic pruning SUMMARY. The torque required to cut branches is an important parameter for designing a robotic end-effector for pruning apple (Malus ×domestica) trees. In this study, the branch cutting torque was measured because it is important for the future development of a robotic pruning end-effector. To measure the branch cutting torque, a force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There was little difference between plants that had received renewal pruning and thinning and renewal pruning only in 2021, although thinned plants possessed slightly higher quality fruits. Therefore, we do not recommend thinning pruning following renewal pruning, since the benefits of thinning do not outweigh the added pruning labor expense, which is one of the costliest components of fruit production (Lorenzo et al 2022;Strik et al 2003;Zahid et al 2022). The size, appearance and fruit production capacity displayed by renewal-pruned plants in 2022 was analogous to three-year-old plants established in a new orchard in 2012 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There was little difference between plants that had received renewal pruning and thinning and renewal pruning only in 2021, although thinned plants possessed slightly higher quality fruits. Therefore, we do not recommend thinning pruning following renewal pruning, since the benefits of thinning do not outweigh the added pruning labor expense, which is one of the costliest components of fruit production (Lorenzo et al 2022;Strik et al 2003;Zahid et al 2022). The size, appearance and fruit production capacity displayed by renewal-pruned plants in 2022 was analogous to three-year-old plants established in a new orchard in 2012 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, automatic pruning could effectively avoid the quality degradation caused by incorrect pruning by selecting appropriate pruning points (He and Schupp, 2018). Robotic selective pruning has achieved remarkable results on grapes and apples, but the relevant technologies are still in the experimental stage (Botterill et al, 2017;Zahid et al, 2020;Zahid et al, 2021). The automatic pruning technology of open-center jujube trees with variable structures needs to be studied in-depth.…”
Section: Introductionmentioning
confidence: 99%
“…Pruning is essential, especially in modern high-density operations (Sus et al 2018), and represents approximately 30% of the apple production costs for trees trained as central leaders (Ferree 1976) and vertical axe (Marini and Barden 2004). Manual pruning is one of the most labor-intensive operations in an orchard (Mika et al 2016;Zahid et al 2022). To reduce pruning costs, previous studies reported experiments involving central leader trees being hedged during the dormant season (Ferree 1976;Hansen et al 1968) and semi-dwarf trees being hedged in summer (Ferree 1984).…”
mentioning
confidence: 99%